Contemporary Issues and Research in Operations Management - Moynihan, Gary P. (IntechOpen, 2018)
Operations management (OM) is the function concerned with the planning, design, implementation, and control of business operations in the production of goods and services. OM has expanded from its original factory-centric orientation to encompass the service industry and the respective, accompanying supply chains, with a broad, global range of applications, increasing reliance on quantitative analysis, and the development and the use of supporting computer-based information systems and technology. This book highlights some critical aspects and advances in the field of operations management. Topics covered include investigations in the area of sustainable supply chain management; the application of OM principles to the deployment of field laboratories to address epidemics; and novel approaches to applying operations management in response to increasingly diverse requirements, circumstances, and performance criteria.